2020
DOI: 10.1016/j.ccell.2019.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Silencing of CDR1as Drives IGF2BP3-Mediated Melanoma Invasion and Metastasis

Abstract: Highlights d Loss of CDR1as expression promotes melanoma invasion and metastasis d CDR1as arises from a lncRNA that is epigenetically silenced by EZH2/PRC2 d CDR1as interactor, IGF2BP3, largely mediates the effects of CDR1as loss in melanoma d CDR1as levels associate with cell states and therapeutic sensitivities

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
193
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 233 publications
(198 citation statements)
references
References 107 publications
(123 reference statements)
5
193
0
Order By: Relevance
“…However, we should acknowledge the limitations of this work: 1) the lack of in vivo animal model results to strengthen the importance of HAND2-AS1/miR-590-3p/ KCNT2 triplets in GC development; and 2) we did not investigate the upstream mechanism that is responsible for the elevated expression status of HAND2-AS1 in GC. There are studies showed epigenetic modifications can affect lncRNA expression in cancers, 22,23 which may be a mechanism for the decreased expression of HAND2-AS1 and deserves to be deeply investigated in the future.…”
Section: Hand2-as1 Regulates Gc Cell Behaviors Via Regulating Mir-590mentioning
confidence: 99%
“…However, we should acknowledge the limitations of this work: 1) the lack of in vivo animal model results to strengthen the importance of HAND2-AS1/miR-590-3p/ KCNT2 triplets in GC development; and 2) we did not investigate the upstream mechanism that is responsible for the elevated expression status of HAND2-AS1 in GC. There are studies showed epigenetic modifications can affect lncRNA expression in cancers, 22,23 which may be a mechanism for the decreased expression of HAND2-AS1 and deserves to be deeply investigated in the future.…”
Section: Hand2-as1 Regulates Gc Cell Behaviors Via Regulating Mir-590mentioning
confidence: 99%
“…We look forward to seeing in future studies whether the ndings of this paper apply to other tumors, such as ovarian cancer or even to other diseases. Previous reports revealed that a certain circRNA formed by cyclization of lncRNA may have different functions and mechanisms in different biological process, such as the CDR1as [21,48,49]. Thus, future iterations of comprehensive understanding of circCDKN2B-AS1 biogenesis, binding proteins/microRNAs, effects on aerobic glycolysis and tumorigenesis programs may in fact demonstrate even greater potency.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of circRNAs on the development in various cancers has been reported, such as breast cancer, oral cancer and hepatocellular carcinoma [14][15][16], Most of the discoveries revealed that circRNAs can function by sponging microRNAs and regulating the expression level of target genes [17][18]. Recent studies revealed that circRNAs can bind with RNA binding proteins (RBPs) [19][20][21], however, the potential value of circRNAs-RBP complex is still elusive and the biological function of most circRNAs in clinic is still unkonwn.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that glutathione can be a metabolic link between drug-induced dedifferentiation and sensitivity to ferroptosis-inducing agents, and this was confirmed by supplementation of the culture medium with GSH that rescued melanoma from ferroptosis [193]. Recently, cerebellar degeneration-related 1 antisense (CDR1as) has been identified as a novel marker of melanoma cell differentiation state, and depletion of CDR1as was associated with the metastatic potential of melanoma [197]. It has been found that CDR1as high cells were substantially more sensitive to inhibitors of GPX4, thus induction of ferroptosis.…”
Section: Ferroptosis In Melanomamentioning
confidence: 91%
“…It has been found that CDR1as high cells were substantially more sensitive to inhibitors of GPX4, thus induction of ferroptosis. In addition, high levels of CDR1as have been preferentially associated with melanoma cell state marked by low MITF level and high AXL level [197]. Thus, expression of CDR1as may serve as a determinant of phenotypic state of melanoma cells that may be targeted by inducers of ferroptosis.…”
Section: Ferroptosis In Melanomamentioning
confidence: 99%